2020
DOI: 10.5194/bg-17-3723-2020
|View full text |Cite
|
Sign up to set email alerts
|

Salinity-dependent algae uptake and subsequent carbon and nitrogen metabolisms of two intertidal foraminifera (<i>Ammonia tepida</i> and <i>Haynesina germanica</i>)

Abstract: Abstract. Benthic foraminifera are abundant marine protists which play an important role in the transfer of energy in the form of organic matter and nutrients to higher trophic levels. Due to their aquatic lifestyle, factors such as water temperature, salinity and pH are key drivers controlling biomass turnover through foraminifera. In this study the influence of salinity on the feeding activity of foraminifera was tested. Two species, Ammonia tepida and Haynesina germanica, were collected from a mudflat in no… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 54 publications
(70 reference statements)
0
19
0
Order By: Relevance
“…species Ammonia tepida increased with salinity (Lintner et al, 2020). In the same study, both species showed large differences in the retention of C relative to N, with subsequent adverse effects on the re-cycling of these elements by mineralization/respiration and excretion to the environment.…”
Section: General Informationmentioning
confidence: 63%
See 4 more Smart Citations
“…species Ammonia tepida increased with salinity (Lintner et al, 2020). In the same study, both species showed large differences in the retention of C relative to N, with subsequent adverse effects on the re-cycling of these elements by mineralization/respiration and excretion to the environment.…”
Section: General Informationmentioning
confidence: 63%
“…The mean C uptake recorded at 20 PSU showed a maximum five days after food addition and declined thereafter. Such a behavior is already known from H. germanica (Lintner et al, 2020), a closely related species living in the same habitat. In Lintner et al (2020) this behavior was explained by the fact that H. germanica also contained kleptoplasts, which may serve as internal C and N sources via digestion.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations